Educational Facility Needs Based on School-Age Population Growth: Evidence from Poso Regency, Indonesia - Lagonda, Prilly Prichila; Setyono, Jawoto Sih (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the availability and distribution of educational facilities in Poso Regency in 2026. A quantitative descriptive approach was employed using secondary data collected through document analysis from official sources. The analysis was conducted based on the SNI 03-1733-2004 standard to compare the required number of educational facilities with existing availability across all subdistricts in Poso Regency. Population projection using the geometric method estimates that the school-age population will reach 223,190 in 2026, which serves as the basis for calculating facility needs. The results indicate that, overall, the availability of educational facilities in Poso Regency is relatively sufficient at the kindergarten, primary school, and junior high school levels, where the number of available facilities exceeds the calculated requirements. However, at the senior high school level, a deficit of 27 units was identified. In addition, the distribution of educational facilities remains uneven across subdistricts, as several areas still lack any senior high school facilities. This study contributes to educational planning by providing a data-driven assessment of facility adequacy based on school-age population needs. From a policy perspective, the findings highlight the need to prioritize the development and equitable provision of senior high school facilities, particularly in underserved subdistricts. Strategic efforts should focus on increasing the number of schools and improving the distribution of facilities to ensure more equitable access to education.